Kemampuan Pemecahan Masalah Matematis Mahasiswa pada Pembelajaran Preprospec Berbantuan TIK - Dewi (Nino Adhi), Nuriana Rachmani; Munahefi, Detalia Noriza; Azmi, Kholifatu Ulil (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2020)
The purpose of this research is to analyze the achievement of studentsâ€™ mathematical problem solving ability as the result ofÂ implementation of ICT-assisted Preprospec learning and conventional learning. This research used quantitative methods. Two sample groups (experiment group and control group) were selected randomly from groups of students in the Study Program of Mathematics Education who enrolled in Integral Calculus course. An experiment group was taught by using ICT-assisted Preprospec learning. Result from this research are (1) The overall achievement of students' mathematical problem-solving ability who were taught by using ICT-Assisted Preprospec Learning and for this type of middle mathematical prior knowledge was better than those who were taught by using conventional learning (2) The achievement of mathematical problem solving ability of students who were taught by using ICT-assisted preprospec learning for upper and lower mathematical prior knowledge are similary than the achievement of those who were taught by using conventional learning.Tujuan dari penelitian ini adalah untuk menganalisis pencapaian kemampuan pemecahan masalah matematis pada Pembelajaran Preprospec Berbantuan TIK. Metode kuantitatif adalah metode yang digunakan dalam penelitian ini. Adapun sampelnya diambil secara acak dari seluruh mahasiswa Program Studi Pendidikan Matematika Jurusan Matematika pada salah satu perguruan tinggi negeri di Semarang yang mengambil mata kuliah Kalkulus Integral. Hasil penelitian ini adalah (1) Pencapaian kemampuan pemecahan masalah matematis mahasiswa yang mendapatkan Pembelajaran Preprospec Berbantuan TIK secara keseluruhan dan untuk jenis kemampuan awal matematis sedang lebih baik daripada mahasiswa yang mendapatkan pembelajaran konvensional; (2) Pencapaian kemampuan pemecahan masalah matematis mahasiswa yang mendapatkan Pembelajaran Preprospec Berbantuan TIK untuk kemampuan awal matematis atas dan bawah setara dengan mahasiswa yang mendapatkan pembelajaran konvensional.